Assessment of the Relationship between Financial Integration and Industrial Sector Growth: Evidence from Nigeria - , Ezeaku, Hillary Chijindu, A. Anidiobu Gabriel, I. P. Okolie Paschal (Archives of Current Research International, 2017)
This study assessed the relationship between financial integration and industrial sector growth in Nigeria. One of the major goals of financial integration is to boost investments and engender increased productivity among nations. In this study, we examined how international financial integration has impacted on the Nigerian industrial sector using annualized data from 1981 to 2014. The study employed the vector autoregressive (VAR) estimation in analyzing a modified growth model. The Johansen co-integration test and the VAR-Granger causality test were also utilized. From the unit root test, no evidence of long-run relationship was found to exist between financial integration and industrial growth over the study period - both at the instances of the Trace statistic and the Max-Eigen test statistic. The study found that trade openness and foreign direct investment have positive but insignificant impact on the Nigerian industrial sector whereas financial market development exerted negative impact on industrial growth in Nigeria. No evidence of causal link was found between growth in industrial value added, openness and financial market development. However, we found evidence of unidirectional causality running from foreign direct investment to industrial value added. The study concludes that international financial integration has not exerted significant positive influence on the growth and development of the Nigerian industrial sector and therefore, recommends that policy actions aimed at promoting exports and building an import substitution economy be put in place.